Unveiling the anode reaction environment in a CO2 electrolyzer to provide a guideline for anode development - Song, Ji Hwan; Ka, SeoHyeon; Lim, Chulwan; Han, Man Ho; Lee, Dong Ki; Oh, Hyung-Suk; Lee, Woong Hee (Royal Society of Chemistry, 2023)
The use of 3d transition metals, such as Ni-based electrodes for the oxygen evolution reaction (OER) is inhibited in membrane electrode assembly (MEA) CO2 electrolyzers owing to the local acidic media. We unveiled the reaction environment of the anode during the CO2 reduction reaction (CO2RR) with ex situ characterization and in situ/operando pH measurements to challenge the employment of Ni-based electrodes for OER in MEA. Despite the neutral anolyte, the reaction environment became acidic because of the transported carbonate ions and drastic pH fluctuations (acidic to weakly alkaline) created by the nonuniform ion and water distribution. This pH fluctuation causes a rapid phase transition of Ni between hydrated hydroxide and dissolved ions, causing severe degradation and dissolution. Based on these insights, we propose a guideline for selecting OER electrodes for MEA CO2 electrolyzers: good acidic stability with no phase transition under high anodic potential between acidic and weakly alkaline media is required.